2030 : a day in the life of tomorrow's kids - Zuckerman, Amy.; Daly, James; Manders, John (New York : Dutton Children's Books, 2009)
Examines trends and scientific and technological research to speculate what a typical day will be like for a child living in the year 2030.
Includes bibliographical references.
Booklist
School Library Journal
5.6
3-6
3-6
Keywords: Technological forecasting -- Juvenile literature; Technological innovations -- Forecasting -- Juvenile literature; Twenty-first century -- Forecasts -- Juvenile literature; Technological forecasting; Technological innovations; Twenty-first century; Technological forecasting; Technological innovations; World history -- 21st century